GAMBARAN KADAR BIOCHEMICAL OXYGEN (BOD) DAN CHEMICAL OXYGEN DEMAND (COD) PADA LIMBAH CAIR INDUSTRI TAHU - Kahar, Kahar; Prasetia, Bunga (Poltekkes Kemenkes Bengkulu, 2023)
Wastewater is a combination of liquids or water or waste generated from household, institutional, commercial, and industrial activities that can cause various problems, one of which is the tofu industry that produces liquid and solid waste, especially liquid waste can cause environmental problems and pollution if not treated first. The wastewater quality standard for soybean processing activities includes Biochemical Oxygen Demand (BOD), Chemical Oxygen Demand (COD), Potential Hydrogen (pH), and Total Suspended Solid (TSS). The aim of this study is to determine the levels of BOD and COD in the liquid waste. This is a descriptive study with a population of workers from a tofu Industry, using a total population sampling technique, and wastewater samples were taken from the effluent discharge and examined in the laboratory. The sampling technique used was grab sampling. The results of the examination of BOD and COD in the wastewater of the tofu Industry were an average of 3,191 mg/L for BOD and 9,308.67 mg/L for COD. The conclusion is that the high levels of COD and BOD in the tofu Industry do not meet the standards.